2017
DOI: 10.15252/embj.201797212
|View full text |Cite|
|
Sign up to set email alerts
|

Complete suppression of Htt fibrilization and disaggregation of Htt fibrils by a trimeric chaperone complex

Abstract: Huntington's disease (HD) is a neurodegenerative disorder caused by an expanded CAG trinucleotide repeat in the huntingtin gene (). Molecular chaperones have been implicated in suppressing or delaying the aggregation of mutant Htt. Using and assays, we have identified a trimeric chaperone complex (Hsc70, Hsp110, and J-protein) that completely suppresses fibrilization of HttExon1Q The composition of this chaperone complex is variable as recruitment of different chaperone family members forms distinct functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
155
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(162 citation statements)
references
References 49 publications
6
155
1
Order By: Relevance
“…However, it remains poorly understood to what extent chaperones are capable of disassembling already existing amyloids, given their high thermodynamic stability (Baldwin et al, 2011). Only for α synuclein and HTTExon1Q 48 it has been established that the human Hsp70 machinery is able to disassemble preformed fibrils in vitro (Gao et al, 2015;Scior et al, 2018). Here we investigate the broader role of this machinery in amyloid biology by testing its potential to process aggregates of amyloidogenic Tau isolated from cells or produced in vitro and by characterizing more precisely the products of chaperone-mediated Tau disaggregation.…”
Section: Discussionmentioning
confidence: 99%
“…However, it remains poorly understood to what extent chaperones are capable of disassembling already existing amyloids, given their high thermodynamic stability (Baldwin et al, 2011). Only for α synuclein and HTTExon1Q 48 it has been established that the human Hsp70 machinery is able to disassemble preformed fibrils in vitro (Gao et al, 2015;Scior et al, 2018). Here we investigate the broader role of this machinery in amyloid biology by testing its potential to process aggregates of amyloidogenic Tau isolated from cells or produced in vitro and by characterizing more precisely the products of chaperone-mediated Tau disaggregation.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has been provided that molecular chaperones, especially Hsp70 and Hsp40, can prevent formation of amyloid fibers (Muchowski et al 2000) or disaggregate them (Gao et al 2015), showing the potential of modulating the PN to combat proteinopathies in vivo. Accordingly, pharmacological induction or genetic overexpression of molecular chaperones has been shown to prevent aggregation in cellular (Sittler et al 2001) and animal models (Labbadia et al 2012;Kakkar et al 2016;Nagy et al 2016;Scior et al 2018).…”
Section: Ameliorating Proteinopathiesmentioning
confidence: 99%
“…HSP-110 has been previously identified in a genome-wide screen for proteostasis regulators in C. elegans , in which an organism-wide KD of HSP-110 reduced Q35 aggregation (Silva et al, 2011). In contrast, the same systemic KD resulted in increased Q35 aggregation in another study (Scior et al, 2018). The respective outcome is likely to depend on the timing and strength of the KD, and to what extent it affects the folding of proteins other than Q35, both in the same tissue and in neighboring tissues, which may also influence muscle cell proteostasis through non-autonomous mechanisms (Morimoto, 2019; Shai et al, 2014).…”
Section: Discussionmentioning
confidence: 90%
“…While previous work revealed that metazoan cells exhibit disaggregation activity and also contain all co-factors required for cytosolic propagation and dissemination of an ectopically expressed amyloid-like yeast prion (Cohen et al, 2006; Hofmann and Vorberg, 2013; Hofmann et al, 2013; Krammer et al, 2009a; Krammer et al, 2009b), the nature of these co-factor(s) was still unclear, since direct homologs of HPS104 are absent from the metazoan cytosol. The recent discovery of a metazoan disaggregation machinery in which a particular HSP110-type nucleotide exchange factor (NEF) cooperates with the human HSP70-DNAJ system to fragment and depolymerize amyloid aggregates (Gao et al, 2015; Scior et al, 2018) has raised the question of whether this activity could prevent or promote the prion-like propagation of amyloid-type aggregates in metazoans and what physiological implications this would have. Since prion-like amplification and intercellular spreading of disease-linked proteins is implicated in the propagation of the pathology in neurodegenerative diseases such as AD and PD, co-factors involved in this process might be potential therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%